PEMBERDAYAAN EKONOMI MASYARAKAT SEKITAR PESANTREN STUDI: BANK WAKAF MIKRO AL FITHRAH WAVA MANDIRI SURABAYA - Siti Aisyah (IZZI: Jurnal Ekonomi Islam, 2021)
The focus of this study aims to analyze the role of the waqf bank miko al Fithrah Wava Mandiri Surabaya in empowering micro business actors around the pesantren. This research uses qualitative research with a comparative study approach. The data collection technique uses observation, interviews, and documentation on the empowerment of the economic community of micro business actors around the pesantren at Bank Wakaf Mikro Surabaya. The collected data is then processed and analyzed with a descriptive-qualitative mindset. The results showed that the economic empowerment of micro business actors around Islamic boarding schools in micro waqf banks through community assistance called HALMI (weekly halaqah).